Endogenous deposit dollarization - Christian Broda; Eduardo Levy Yeyati (Federal Reserve Bank of New York, 2003)
This paper explores sources of deposit dollarization unrelated to standard moral hazard arguments. We develop a model in which banks choose the optimal currency composition of their liabilities. We argue that the equal treatment of peso and dollar claims in the event of bank default can induce banks to attract dollar deposits above the socially desirable level. The distortion arises because dollar deposits are the only source of default risk in the model, but dollar depositors share the burden of the default with peso depositors. The incentive to dollarize is reinforced by common banking system safety nets such as deposit and bank insurance. Our findings suggest that regulators in bi-currency economies would potentially benefit by departing from the currency-blind benchmark and differentiating among currencies in a way that prevents undesirable currency mismatches
Keywords: G11; G21; F31; 330; Währungssubstitution; Einlagengeschäft; Einlagensicherung; Theorie